2013
DOI: 10.1016/j.jocrd.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' “not just right experiences” predict obsessive–compulsive symptoms in their sons: Family study of a non-clinical Italian sample

Abstract: The heart of the obsessional process may be considered the subject's underlying impression that -something is wrong‖. Therefore, the phenomenon labeled -not just right experiences‖ (NJREs) has increasingly been receiving attention since it captures the subjective sense that -something isn't just as it should be‖. In the present study we sought to add to the evidence that NJREs may be a putative psychological marker of OCD. To this aim, measures of NJREs, obsessive-compulsive (OC) symptoms and OC-related cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 101 publications
0
7
0
1
Order By: Relevance
“…As a matter of fact, in most of studies on nonclinical samples, as many as 80% or more of the participants reported such experiences on the NJRE-Q-R (Coles et al, 2003;Cougle et al, 2011;Ghisi et al, 2010;Sica et al, 2013). In addition, in all studies where the NJRE-Q-R severity has been used, the correlation between this measure and the OC symptoms was in the moderate range (e.g., Coles et al, 2003: around .45;Ghisi et al, 2010: .42;current study: from .46 to .56).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of fact, in most of studies on nonclinical samples, as many as 80% or more of the participants reported such experiences on the NJRE-Q-R (Coles et al, 2003;Cougle et al, 2011;Ghisi et al, 2010;Sica et al, 2013). In addition, in all studies where the NJRE-Q-R severity has been used, the correlation between this measure and the OC symptoms was in the moderate range (e.g., Coles et al, 2003: around .45;Ghisi et al, 2010: .42;current study: from .46 to .56).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of an association between NJREs and OCD or OC symptoms appears robust so far (for a review, see Sica, Caudek, Chiri, Ghisi, & Marchetti, 2012;Sica et al, 2013;Taylor et al, 2014). On the other hand, only a few studies provided data about the specificity of this construct to OCD or OC symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from 16 samples ( N =5,940 participants) were included in the meta-analysis (Chik, Calamari, Rector, & Rieman, 2010; Coles et al (2003, Studies 1 and 2, based on different samples); Coles, Heimberg, Frost, & Steketee, 2005; Cougle, Fitch, Jacobson, & Lee, 2013 (Study 2); Cougle, Goetz, Fitch, & Hawkins, 2011; Cruz-Fuentes, Blas, Gonzalez, Camarena, & Nicolini, 2004; Ecker & Gönner (2008, 2011 with each study reporting different correlational data); Ghisi, Chiri, Marchetti, Sanavio, & Sica, 2010; Neal & Cavanna, 2013; Olatunji, Unoka, Beran, David, & Armstrong, 2009; Pietrefesa & Coles, 2008; Sica et al, 2013; Sica, Caudek, Chiri, Ghisi, & Marchetti, 2012; Sparrow, 2009; Summerfeldt, 2006). The correlations extracted from these studies along with other details on included and excluded samples appear in Appendices A and B.…”
Section: Methodsmentioning
confidence: 99%
“…En consecuencia, y según las teorías cognitivo-conductuales, las creencias que mantienen los padres, pero no las madres, podrían constituir un factor de vulnerabilidad para el desarrollo de síntomas hipocondríacos en sus descendientes. Resultados similares fueron encontrados en estudios sobre el trastorno obsesivocompulsivo, donde se analizó la relación entre las creencias de los progenitores y sus descendientes, en relación a las experiencias "not just right" (Sica et al, 2013) o la "looming vulnerability" (Riskind, Sica, Bottesi, Ghisi, y Kashdan, 2017). En estos estudios se observó que las creencias de los padres jugaban un papel más relevante que las de las madres en la predicción de las creencias de sus descendientes.…”
Section: Discussionunclassified